The young Mozart: digital storytelling with elementary aged students - Horton, Staci (Kansas State University, 2011)
Who was Johannes Chrysostomus Wolfgangus Theophius Mozart? He was a child prodigy who dazzled Kings, Queens, Emperors and Empresses as a young boy and lead an remarkable life in his first ten years. The facts of Mozart’s childhood are known and available, however the vast majority of research is devoted to Mozart’s music, life and career during his adult years. Perhaps the time for a child to begin to realize the importance of Mozart in history would be to create a connection between young Mozart’s daily activities to a student of parallel age. The purpose of the study is to illuminate the life of the child prodigy Wolfgang Mozart using creative digital storytelling for elementary aged students. Due to the awarding of a grant from the National Endowment for the Humanities, research concerning Mozart’s rise and fall in fame was completed in Vienna, Austria, June 21 through July 16, 2010. The resulting focus of the research was to bring awareness to the minds of elementary students of Mozart’s child prodigy years. Using digital storytelling, listening maps, and composition projects, students will step into the world of Mozart as a composer and begin to relate his life to theirs. Data analysis will establish the effective use of digital storytelling to reveal the student’s ability to correlate the boyhood life of Mozart with the master composer. The study was completed in a pilot program in McPherson, Kansas in January 2011.
Keywords: Horton; Mozart; Digital storytelling; Story; Elementary education; Music; Elementary Education (0524); Music (0413); Music Education (0522)